Liquid Organic Fertilizer Alcohol Waste Enriched Manure Effect on Growth and Yield of Chili (Capsicum Annum L.) - Wiyono; Dwi Susilo Utami; Choirul Fariawan Putra; Achmad Fatchul Aziez (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2021)
Alcohol factory waste which still contains a number of nutrients when enriched with manure is good enough to increase the growth and yield of chili. This research was conducted in Jengglong, Jatisobo Village, Polokarto District, Sukoharjo Regency which took place from September 2019 to January 2020. This study used a completely randomized design with two factors and three replications. The first factor consists of 3 levels of Liquid Organic Fertilizer: waste alcohol + EM4, waste alcohol + EM4 + goat manure, alcohol waste + EM4 + a combination of 3 manure (chicken, goat, cow). The second factor dosage of liquid organic fertilizer consists of 4 levels: 0, 1000, 2000, 3000 l/ha. The results of the study showed that the kind and dosage of liquid organic fertilizer enriched with manure did not significantly affect the growth and yield of chili, but the interaction of the two treatments had a significant effect on the yield of chili. The highest weight of red chili was obtained in the treatment of waste alcohol + EM4 + a combination of 3 manure (chicken, goat, cow) with a dose of 3000 l/ha. In conclusion, the use of alcohol waste for fertilization, especially chili plants, should be combined with manure in order to obtain maximum results. The implication of this research is that for fertilizing chili plants, it is better to use alcohol waste, EM4 and a combination of chicken, goat and cow manure at a dosage of 3000 l/ha.